Adherence to anti-tuberculosis treatment among patients in urban field practice area of medical college, Davangere, Karnataka: a qualitative study - R. G., Geethalakshmi; D'souza, Madonna J.; ., Ashok (International Journal Of Community Medicine And Public Health, 2019)
Background: Despite effective diagnosis and free treatment, prevalence of TB is still growing. DOTS was introduced by WHO in 1997, which is more than two decades ago. It’s a known fact in TB that adherence is less due to long duration of treatment and stigma associated with it. This study was conducted with the objective of estimating and the reasons for the non- adherence to anti tuberculosis treatment in urban field practice area of SSIMS & RC, Davangere. Methods: A qualitative method of study design was used. 20 TB patients who are on anti-tuberculosis treatment were interviewed with a structured questionnaire for adherence to treatment. Among them patients who were non adherent were further interviewed in depth to know the reasons for non-adherence. Results: Data analysis resulted in extraction of five themes, which were side effects, financial burden and social support, duration of treatment, food insecurity, unawareness of consequences of non-adherence to treatment. Conclusions: Patient adherence to treatment is multi-factorial and involves individual patient factors, provider factors, and community factors. Addressing issue of non-adherence to treatment requires enhanced efforts towards resolving medical problems like adverse drug effects, developing short duration treatment regimens, motivational counselling, social, family support for patients and improving awareness about disease.